Climate Change Projections for Tanzania Based on High-Resolution Regional Climate Models From the Coordinated Regional Climate Downscaling Experiment (CORDEX)-Africa - Luhunga, Philbert Modest; Kijazi, Agnes L.; Chang'a, Ladislaus; Kondowe, Afredy; Ng'ongolo, Hashim; Mtongori, Habiba (Frontiers in Environmental Science, 2018)
The projected impacts of climate change will further compromise social-economic developments in developing countries, which are already overstretched by the challenges of increasing climate variability. Lessening the impacts and sustaining socio-economic development requires informed, appropriate and adequate adaptation strategies that are scientifically sound and robust. It is therefore important to conduct scientific research to enhance understanding of the possible pathways of future climate change under different emission scenarios as pre-requisite inputs for development of effective adaptation strategies. In this study, climate change projections for Tanzania is carried out using outputs of high resolution Regional Climate Models (RCMs) from the Coordinated Regional Climate Downscaling Experiment program (CORDEX). Simulated daily rainfall, minimum and maximum temperatures for historical climate (1971-2000) and future climate projection (2011-2100) under two Representative Concentration Pathways (RCPs): RCP 8.5 and RCP 4.5 are compared. The comparison is based on determining the departure of present (2011-2040), mid (2041-2070) and end (2071-2100) centuries climate conditions from historical (1971-2000) climate condition. Results indicate warmer future, especially over the highlands. In comparison with other regions, Coastal regions are projected to have a relatively lower increase in temperatures and relatively higher increase in rainfall under both RCP 8.5 and RCP 4.5 emission scenarios. The western regions and southwestern highlands are projected to have a future with decreased rainfall under both RCP 8.5 and RCP 4.5 emission scenarios.